PERUBAHAN SISTEM SPASIAL RUMAH TINGGAL BERFUNGSI GANDA DI DAERAH UMBULHARJO YOGYAKARTA - Hartiningsih, Mrs (Institut Seni Indonesia Yogyakarta, 2008)
A large numberof college students coming from numerous cities in Indonesia hasencouraged citizens of Umbulharjo an area in the city of Yogyakarta to use a part of theirhouses available for the students to rent thereby called double function houses Thisphenomenon is very important and has inspired this research on the change of spatial system among double function houses in Umbulharjo The approach used in this research isQualitative deductive Phenomenology Modified from Ihalauw 1985 Muhajir 1992 and Sudaryono 2004 The population was all double function houses in Umbulharjo YogyakartaFrom the observations It is obvious that there are three basic types of double function housesi e house functions as a dorm house functions as afood selling vendor warung smallrestaurant and house functions as a shop Based on the analysis of the change of spatial systemit was found that there are differences between the change pattern and shape of houses function as a dorm and houses function as a warung restaurant and a shop However the changing process and motivation behind it was similar The main motivation was social and economic.Key words : Spatial system the change pattern and shape social and economicmotivation